PENGARUH MODEL PEMBELAJARAN PERSONALIZED SYSTEM OF INSTRUCTION (PSI) TERHADAP HASIL BELAJAR ELEMEN RENCANA BIAYA DAN PENJADWALAN KONSTRUKSI BANGUNAN PADA SISWA KELAS XI DESAIN PEMODELAN INFORMASI BANGUNAN SMK NEGERI 2 BINJAI - Reyfaldo Sinurat; Rachmat Mulyana (STKIP Subang, 2026)
The learning process in class XI DPIB at SMK Negeri 2 Binjai still shows low student learning outcomes due to the use of less varied instructional models that do not optimally engage students. Therefore, it is necessary to implement the Personalized System of Instruction (PSI) model, which presents learning materials in a structured and systematic manner. This study aims to determine whether the PSI learning model has a better effect than the Direct Instruction model on student learning outcomes in the element of Cost Estimation and Construction Scheduling. This research is motivated by the fact that many students in class XI DPIB 2 at SMK Negeri 2 Binjai have not yet reached the minimum competency standard (KKM) in their daily test scores. The study was conducted in the odd semester of the 2025/2026 academic year using a quasi-experimental method, comparing the learning outcomes of students taught using the PSI model and the Direct Instruction model. Data were collected through a multiple-choice test consisting of 31 items that had been tested and declared valid. The results of the study indicate that students taught using the Personalized System of Instruction model achieved higher learning outcomes than those taught using the Direct Instruction model. The average learning outcome of students taught with the PSI model reached 82%, while those taught with the Direct Instruction model achieved only 75%. The results of the hypothesis testing show that thitung = 2.828223 and ttabel = 1.67155, which means that thitung > ttabel. Therefore, the null hypothesis (H₀) is rejected and the alternative hypothesis (Hα) is accepted. Based on these findings, it can be concluded that the Personalized System of Instruction model has a significant effect on learning outcomes in the Cost Estimation and Building Construction Scheduling element at SMK Negeri 2 Binjai.